PENINGKATAN KEPEMIMPINAN PENGURUS TAHFIDZUL QUR’AN BANAT PONDOK PESANTREN AL-HIKMAH MELALUI PELATIHAN DAN PENDAMPINGAN PENYUSUNAN PROGRAM KERJA: THE INCREASING THE LEADERSHIP OF THE TAHFIDZUL QUR’AN BANAT ISLAMIC BOARDING SCHOOL MANAGEMENT THROUGH TRAINING AND ASSISTANCE IN PREPARING WORK PROGRAMS. - Khumaimah, Rina Rinatul (PADIMAS, 2024)
tahfidzul Qur’an educational iinstitutions will be successful in producing quality output of qur’an memorizers if they have a clear work program. A good work program will also have a good impact if it is carried out accordance with the work program template that has been created and controlled bay a management system that is aware of leadership responsibilities. Field facts show that the management is not running optimally due to a lack of awareness of responsibility, work programs that have not been neatly arranged, which has a impact on students memorizations conditions. Therefore it is verry necessary for the managers of tahfidzul qur’an to be given training and assistance in the preparation of work programs in order to improve the leadership of the management of tahfidzul qur’an banat Al-Hikmah boarding school. Community service activities are carried out in tahfidzulqur’an program at Al-Hikmah Binangun Singgahan Tuban with the number of participants being 7 daily administrators starting from 3o may to 30 june 20204. To find out the results of the PKM , interview, observations and documentation were carried out. After training and mentoring there was a change in leadership from yhe management and clarity of the work program so that activities ran well.